Implications of schedule irregularity as a minimum wage response margin - Michael R. Strain; Jeffrey Clemens (American Enterprise Institute (AEI), 2019)
Empirical research on minimum wages has historically focused on employment effects, with the implicit assumption that workers who remain employed under a minimum wage regime are better off. This paper develops a simple model and a stylized example to highlight the importance of an underappreciated margin: how a minimum wage might affect the regularity of workers' schedules. Our analysis illustrates a novel line of intuition for how a minimum wage can reduce welfare even if, as in our example, it increases wages, productivity, and output, without decreasing employment.
Keywords: A; 330; Minimum Wage; employment; productivity